2020
DOI: 10.3892/ol.2020.11929
|View full text |Cite
|
Sign up to set email alerts
|

Members of the miR‑30 family inhibit the epithelial‑to‑mesenchymal transition of non‑small‑cell lung cancer cells by suppressing XB130 expression levels

Abstract: MicroRNAs (miRs) are associated with cancer metastasis. Aberrant expression levels of members of the miR-30 family have been observed in non-small-cell lung cancer (NSCLC). However, the effects of miR-30 family members on the epithelial-to-mesenchymal transition (EMT) of NSCLC cells and the underlying molecular mechanisms have not yet been fully elucidated. The present study investigated the effects of miR-30 family members on EMT, migration and invasion of NSCLC cells and found that overexpression of these mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
7
0
1
Order By: Relevance
“…As oncomirs and tumor suppressors, miRNAs mostly influence processes of cell proliferation and apoptosis. Examples of most investigated miRNAs in various malignant tumors and their targets are listed in Supplementary Table S1 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
See 3 more Smart Citations
“…As oncomirs and tumor suppressors, miRNAs mostly influence processes of cell proliferation and apoptosis. Examples of most investigated miRNAs in various malignant tumors and their targets are listed in Supplementary Table S1 [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ,…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
“…These miRNAs influence proliferation, survival, resistance to chemotherapy and apoptosis, and migration and cancer cell stemness [ 73 , 206 ]. The main targets of deregulated miRNAs in lung tumors are Ras and Myc pathways, PTEN and PI3K/Akt signaling leading to cell proliferation, the p53 pathway, and others influencing resistance to chemotherapeutics and apoptosis [ 65 , 69 , 70 , 71 ]. Cell migration, proliferation, and resistance to chemotherapeutics are influenced by the interaction of miRNA with HIF and TGFβ pathway elements [ 63 , 76 , 158 ].…”
Section: Mirna In Malignant Tumorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Silencing miR-6515-3p has been shown to inhibit the proliferation of NSCLC cells [ 16 ]. Overexpression of miR-30c and miR-30d-3p inhibited the epithelial-to-mesenchymal transition (EMT) in NSCLC cells [ 17 ]. Besides, it has been reported that high expression of miR-492 was associated with poor prognosis of NSCLC patients.…”
Section: Introductionmentioning
confidence: 99%